STUDY OF KNOWLEDGE ATTITUDE AND PRACTICES OF SELF-MEDICATIONS AMONG MEDICAL AND NURSING STUDENTS IN A MEDICAL COLLEGE PUDUCHERRY - Kar, Smita Kar; Narayanasamy, Narayanasamy; Singh, Vrinda; Sharma, Akshata; Vijayasanthi, Vijayasanthi; Asokan, Asokan; Anand, Vivek; Muthumeenatchi, Muthumeenatchi (International Journal of Pharma and Bio Sciences, 2026)
Self-medication is very common in both urban and rural communities. The frequency of self-administered drugs among medical scholars in Puducherry was not known. Hence, this design was accepted to assess the frequency of self-administered drugs among undergraduate MBBS and nursing students. Our study aims to evaluate the knowledge, attitude, and practice of self-medication among medical and nursing students, to compare the self-medication between medical and nursing students, and to evaluate the factors that influence self-medication. A prospective, observational, questionnaire-based study was conducted in which two groups of students were interviewed using a semi-structured pre-validated questionnaire. Ethical approval was obtained from the institutional ethics committee before the initiation of the study. In this study, we found there is a high prevalence of using antibiotics and analgesics as self-medication among medical students when compared to nursing students. This study paves the way for medical students to come forward to understand and reduce the practice of self-medication.